Legal Protection of Children of Female Prisoners in the Women's Prison - Ingrid Angelina Lukito Arif; Nynda Fatmawati O (Journal of Law, Politic and Humanities, 2025)
The objective of this research is to understand and analyze the legislative ratio regarding the age restriction provisions for children of female inmates in women's correctional facilities under Article 62 paragraph (1) of Law Number 22 of 2022 on Corrections. The method used in this research is normative legal research. The results of this research indicate that the rights of young children of female inmates are not fully guaranteed within the existing legal framework. The regulation of this legal protection is still not optimal in determining the age limit for children of female inmates. This research proposes improvements in the policy of age restriction in legal protection for young children of female inmates and contributes to a better understanding of the age restrictions in legal protection for young children of female inmates in correctional facilities.